PENGARUH KEJELASAN SASARAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP SENJANGAN ANGGARAN - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2020)
The aim of the research are to know the effect budget target clarity towrads budgetary slack. To know the effect of organization Commitment towards budgetary slack. To know the effect simultaneously of budget target clarity and organization commitment towards budgetary slack. The method used is regression analysis which is one of the analyzes which aims to determine the effect of one variable to another variable. The result of this research show budget target clarity has an negative significant effect to wards budgetary slack, with significant value is 0,004 is smaller than 0,05. This means that the clearer the budget targets made at Takalar district government agencies, the lower the budgetary gap that accurs. Organization commitment has negative effect towards budgetary slack, with the value of significant is 0.010 smaller than 0,05. It means the employes of government agency at Takalar district have good organization commitment thereby reducing the creation of budgetary slack. Budget target clarity and organizational commitment simultaneously effect towards budgetary slack with the significant value is 0,004 it means is smaller than 0.05. this means that the budget targets are made clearer and the organizational commitment that is high in each employee at the local governmental agency of Takalar district will reduce the occurrence of budget gaps that will occur.